Impact Of Machine Translation on University Students’ Translation Ability: South Eastern University of Sri Lanka as A Model: A special reference to the South Eastern University of Sri Lanka - M.S. Zunoomy; F.H.A. Shibly (Universitas Djuanda, 2021)
Machine Translation (MT) is a unique tool in the field of translation. It is used all over the world. In accordance with, the undergraduates who are following Specialization in Linguistics and Translation at the department of Arabic language from South Eastern University of Sri Lanka face obstacles when they translate between Tamil, English & Arabic. Due to, they focus on MT to translate. According to this, the current research aims to identify the impact of MT on their translation activities. This research uses the descriptive analysis methodology. Primary data were collected from observation and questionnaire that was given to the undergraduates who are following Specialization in Linguistics and Translation at the department of Arabic language from South Eastern University of Sri Lanka in the academic year 2018/2019. Secondary data were gathered from research papers, books, research articles, and websites. The findings of this research declares that the undergraduates in the selected area have desires in the translation field and face the obstacles when translating. Thus, they try to use MT for getting accurate translation, idea of the source text, understanding the unknown words. Due to it, they couldn’t omit the MT in their translation activities. Because, it is easy to use and helps to save the time. At the time, they assume that non-use of MT will effect negatively in their translation ability.